2022
DOI: 10.1007/s11368-022-03401-x
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation of metal-contaminated bottom sediments by the common ice plant (Mesembryanthemum crystallinum L.) in Poland

Abstract: Purpose The aim of the study was to propose a phytoremediation-based approach toward the proper utilization of post-industrial, metal-contaminated bottom sediments. The common ice plant, Mesembryanthemum crystallinum L. (Aizoaceae), an abiotic-stress tolerant, C3/CAM intermediate halophyte, was tested for growth in substrates containing bottom sediments and for biological removal of metal pollutants. In variant tests, the sediments were admixed with non-toxic components to reduce the ecotoxicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The species has emerged as a model plant in studies aimed at understanding the molecular mechanisms of salinity tolerance [ 10 , 11 , 12 , 13 , 14 ] as well as in respect to its use as a halophytic crop species for salinized soils or in cultivation systems using seawater [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. In addition, its heavy metal tolerance and accumulation potential have been studied [ 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The species has emerged as a model plant in studies aimed at understanding the molecular mechanisms of salinity tolerance [ 10 , 11 , 12 , 13 , 14 ] as well as in respect to its use as a halophytic crop species for salinized soils or in cultivation systems using seawater [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. In addition, its heavy metal tolerance and accumulation potential have been studied [ 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…This semi-halophyte plant is capable of shifting its photosynthetic metabolism from C 3 to CAM (Crassulacean Acid Metabolism) and has become a frequent model in physiological and molecular studies (Cushman and Borland 2002). Its unusual properties (Adams et al 1998), especially high resistance to stress as well as heavy metal tolerance, have led to a suggestion for the environmental use of M. crystallinum as a promising and efficient phytoremediator (Kholodova et al 2005, Amari et al 2014, Nosek et al 2019, Śliwa-Cebula et al 2020, 2023. In the case of cadmium, it has been shown that M. crystallinum can accumulate and deposit this metal in plant organs at relatively high levels without showing any overt signs of damage (Nosek et al 2019, Śliwa-Cebula et al 2020.…”
Section: Introductionmentioning
confidence: 99%